Financial Literacy : Teachers' Public and Private School (Educational Management, 2022)
The national curriculum at the Teacher Training Institute (LPTK) produces no difference in financial literacy competencies between teachers in public and private schools. In fact, financial literacy varies among students in private and public schools. The paper focuses on the analysis of teacher competence in public and private schools. The primary data were 22 private and public school teachers and were analyzed using the student test (t-test). The result of the research is that there is no difference in financial literacy between teachers in public and private schools. Teachers as a complement to students' financial literacy. As a result, if students are more social, economic, indifferent between public and private schools, and complemented, the teacher is more competent.